The social determinants of tuberculosis: From evidence to action - Hargreaves, James R.; Boccia, Delia; Evans, Carlton A.; Adato, Michelle; Petticrew, Mark; Porter, John D. H. (American Public Health Association, 2011)
Growing consensus indicates that progress in tuberculosis control in the low- and middle-income world will require not only investment in strengthening tuberculosis control programs, diagnostics, and treatment but also action on the social determinants of tuberculosis. However, practical ideas for action are scarcer than is notional support for this idea. We developed a framework based on the recent World Health Organization Commission on Social Determinants of Health and on current understanding of the social determinants of tuberculosis. Interventions from outside the health sector—specifically, in social protection and urban planning—have the potential to strengthen tuberculosis control.